Sign Language, Democracy and Deafness in Africa - Okombo, Okoth (1999)
Abstract There is evidence all over the world that a sign language giv es a deaf person the best chance of expanding one's space in life. Amo ng those who have this awareness in Africa, there is a tremendous amou nt of enthusiasm to give the deaf people of Africa, as many sign langu age (SL) facilities as possible. The general line of thinking is that deafness is basically a communication disability, and that, if there a re not compounding disabilities, a signing deaf person should have the same opportunities in life as an equally endowed hearing person, othe r factors kept constant. Yet even when this position is accepted, ther e are all sorts of questions that are left unresolved, e.g. What democ ratic institutions will guarantee such deaf-hearing equality? Where sh ould the state come in and what space should be left to the deaf adult s as an individual, and to the deaf-child's domestic care-givers? If t he state cannot control what the deaf child gets at home, what repair mechanisms can be used to correct the damage done at home - without go ing against the canons of democracy? These and other issues of a simil ar nature will constitute the subject of this article.